Acute myocardial injury after administration of intravenous epinephrine for allergic reaction - Zakka, Katerina (SAGE Open Med Case Rep, 2020)
Myocardial injury or infarction in the setting of anaphylaxis can be due to anaphylaxis itself, known as Kounis syndrome, or as a result of treatment with epinephrine. Myocardial ischemia caused by therapeutic doses of epinephrine in the setting of anaphylaxis is a rare event attributed to coronary artery vasospasm. A 41-year-old female with past medical history of recurrent costochondritis, chronic thrombocytopenia, and nonspecific palindromic rheumatism presented to the emergency department with perioral numbness, flushing and throat tightness after a meal containing fish and almonds. Intramuscular epinephrine was ordered but inadvertently administered intravenously, after which she developed sharp, substernal chest pain and palpitations. Electrocardiogram showed normal sinus rhythm with QT interval prolongation. Troponin peaked at 1.41 ng/mL. She was given 324 mg of aspirin in the emergency department. Transthoracic echocardiogram showed normal ejection fraction with lateral wall motion abnormality. We present a case of a patient with no significant risk factors for coronary artery disease who developed myocardial injury following inadvertent IV administration of a therapeutic dose of epinephrine for an anaphylactic-like reaction. The development of myocardial injury after epinephrine is rare, with only six reported cases in literature and just one after intravenous administration. This is the first described case of known myocardial injury without ST-T wave changes on electrocardiogram . The proposed mechanism is an alpha-1 receptor-mediated coronary vascular spasm resulting in myocardial ischemia. The aim of this case is to raise awareness of the potential for acute myocardial injury after inadvertent intravenous administration of epinephrine for anaphylaxis, even in patients with no known risk factors for coronary artery disease, as well as to demonstrate that this clinical scenario can present regardless of troponin elevation and without ST-T wave ECG changes.